Zinc oxide : - Morkoc, Hadis (Wiley-VCH, 2009)
This reference covers the wide and rapidly growing field of biocatalysis. It combines complementary expertise from such areas as microbiology, enzymology, molecular biology structural biology and organic chemistry, thus highlighting the interdisciplinary nature of the subject. With its special focus on progress and new developments towards environmentally beneficial reactions with high levels of selectivity for the production of key compound classes, this book will enlighten both chemists and biologists as to the advances and opportunities existing in enzyme catalysis.